Rancang Bangun Sistem Informasi Pelayanan Penggantian Oli Mobil - Handoko, Handoko; Tjandrarini, A B; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Car oil replacement is one of a must to do list to keeping carâ€™s performance.Â In car oil replacement service term, not all shop has a standard. Car oil replacement time reminder service is still done manually, so that sometimes customers forgot to replace the car oil in time. Promo information only does setting banners in the shop. This resulted process of service provide is not optimal. It cause services is not provided optimally, where it will impact on shop and customerâ€™s loss. Based on this issue, car oil replacement service information system has been made to help provide recommendations appropriate standards as specified for car oil replacement service. This system also can be used to support car oil replacement reminder and booking service which will be done using Short Message Service (SMS).